What is the Thermal Conductivity of Copper? The Production of a Fact Through Scientific Forgetting. Issue 1 (13th October 2021) - Hauser, Elliott
Abstract: What is the thermal conductivity of copper? This straightforward question leads to a fascinating instance of the production of scientific facts through documentation practices. Ho, Powell and Liley's 1974 The Thermal Conductivity of the Elements: A Comprehensive Review is examined as an artifact of scientific reference data production, and its answer to the initial question is traced to modern‐day search engine results. A short history of the Center that produced the book and some initial research into its authors is provided. Kuhn's concepts of normal science and normic lexical structures are utilized to clarify the Comprehensive Review's functioning within the broader scientific fields in which it is utilized. Bowker's concepts of memory practices and the jussive Archive help identify the forgetting embedded in the production of reference data, producing what Star called global certainty. Far from impugning the internal validity of these scientific facts, this forgetting is shown to be licensed by scientific rigor. This paper presents a novel historically informed investigation of how documentation practices produce scientific facts, and connect these activities to modern‐day knowledge graph information retrieval. The theoretical analyses provided show how scientifically licensed forgetting is a key mechanism of fact production, what Hayles termed constrained constructivism.